Clinical proteomics: Promises, challenges and limitations of affinity arrays. Issue 3 (2nd March 2015) - Betzen, Christian; Alhamdani, Mohamed Saiel Saeed; Lueong, Smiths; Schröder, Christoph; Stang, Axel; Hoheisel, Jörg D.
Abstract : After the establishment of DNA/RNA sequencing as a means of clinical diagnosis, the analysis of the proteome is next in line. As a matter of fact, proteome‐based diagnostics is bound to be even more informative, since proteins are directly involved in the actual cellular processes that are responsible for disease. However, the structural variation and the biochemical differences between proteins, the much wider range in concentration and their spatial distribution as well as the fact that protein activity frequently relies on interaction increase the methodological complexity enormously, particularly if an accuracy and robustness is required that is sufficient for clinical utility. Here, we discuss the contribution that protein microarray formats could play towards proteome‐based diagnostics.